Effect of Forensic Accounting Techniques on Fraud Detection in Nigeria Public Sector - Inyada Sunday Joseph (JOURNAL OF ACCOUNTING AND FINANCIAL MANAGEMENT, 2026)
Fraud in public institutions, especially in financial management, remains a critical issue that undermines transparency and accountability, leading to significant financial losses and eroded public trust. The main objective of this research was to evaluate the relationship between these forensic accounting techniques and fraud detection in the public sector, specifically focusing on the Office of the Accountant General of the Federation (OAGF) and similar institutions. This study investigates the effectiveness of forensic accounting techniques, particularly data mining and ratio analysis, in detecting and preventing fraud within the Nigerian public sector. A survey research design was employed, using a well-structured closed-ended questionnaire distributed to 200 staff members from the Budget and Accounts office within the OAGF. The data was collected from both primary and secondary sources and analyzed using simple percentages and T-test statistics to test the hypotheses. The study found a significant positive relationship between both data mining and ratio analysis with fraud detection. Specifically, the t-value for data mining was 10.643 (p < .0001), and the t-value for ratio analysis was 13.666 (p < .0000), indicating that both techniques significantly contribute to fraud detection. Based on these findings, the study recommends enhancing training and capacity-building for public sector employees in forensic accounting techniques, as well as the implementation of comprehensive fraud detection systems that integrate forensic tools with internal controls. These recommendations aim to improve fraud detection, increase transparency, and foster greater public trust in Nigeria’s public financial management. By adopting these strategies, public institutions can strengthen their financial oversight and significantly reduce the risks of fraud.